Pregnancy Complications and Outcomes Among Women With Congenital Heart Disease in Beijing, China - Liu, Yang; Li, Yanna; Zhang, Jun; Zhao, Wenjuan; Bao, Zhaoliang; Ma, Xiaolong; Zhao, Yichen; Zhao, Cheng; Liu, Kemin; Ye, Qing; Su, Lixiao; Yang, Yao; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective: To conduct a comparative analysis of the complications and concomitant diseases in pregnant women with and without congenital heart disease in Beijing, China. Methods: We compared pregnancy-related complications and concomitant diseases experienced by women with and without congenital heart disease throughout 19,424 deliveries in Beijing Anzhen Hospital between 2010 and 2019, including cardiovascular and obstetric factors, fetal events, delivery methods, and other complications over a mean 5-years post-delivery follow-up period. Results: There were 1,040 women with congenital heart disease (5.35% of all deliveries). Compared to women without congenital heart disease, these women had longer hospital stays (7.83±4.65 vs. 4.93±3.26 days) and a higher death rate (1.92 vs. 0.02%). They also had a greater risk of comorbidities, including pre-term delivery (odds ratio: 13.65 vs. 6.71), heart failure (odds ratio: 4.90 vs. 0.40), and arrhythmia (odds ratio 12.69 vs. 4.69). Pulmonary hypertension, New York Heart Association functional class III IV, and no congenital heart disease surgery prior to pregnancy were associated with adverse events such as cesarean section, pre-term delivery, and heart failure. The fetuses of mothers with congenital heart disease were more likely to be born pre-term (odds ratio: 13.65 vs. 6.71) and have low birth weight (odds ratio: 8.56 vs. 4.36). Eleven infants (1.82%) born to mothers with congenital heart disease and four infants (0.64%) born to mothers without congenital heart disease were diagnosed with congenital heart disease. Conclusions: Women with congenital heart disease may be at greater maternal and infant risk during pregnancy and the perinatal period. Pulmonary hypertension, a decrease in cardiac function, and no previous congenital heart disease surgery increase the risk in women with congenital heart disease. Greater attention should be paid to pregnant women with congenital heart disease and their offspring.